Reactivation of Anticancer Immunity by Resetting Interorgan Crosstalk in Immune‐Suppressive Cells with a Nanoparticulated Anti‐Inflammatory Drug. Issue 16 (26th January 2023) - Doi, Mizuki; Tanaka, Hiroki; Ohoto, Takara; Miura, Naoya; Sakurai, Yu; Hatakeyama, Hiroto; Akita, Hidetaka
Abstract: The reactivation of anticancer immunity is a fundamental principle in cancer immunotherapy as evidenced by the use of immune checkpoint inhibitors (ICIs). While treatment with the ICIs is shown to have remarkable and durable therapeutic effects in the responders, the low objective response rate (<40%) continues to be a major problem. Since myeloid‐derived suppressor cells (MDSCs), heterogenous cells with strong immunosuppressive activity that originate in the hematopoietic system, suppress the anticancer immunity via parallel immune checkpoint‐dependent and independent pathways, these cells are potential targets for improving the efficacy of cancer immunotherapy. In this study, it is demonstrated that MDSCs can be depleted by delivering synthetic glucocorticoid dexamethasone to phagocytic cells in the spleen using a lipid nanoparticle. Since the interaction of nanoparticles with T cells is intrinsically poor, this strategy also enables the "detargeting" from T cells, thus avoiding the nonspecific suppression of cytotoxic immune responses against cancer cells. In addition to the direct anticancer effect of the nanoparticulated dexamethasone, their synergistic anticancer effect with ICIs is also reported. Abstract : Administration of lipid‐based nanoparticles containing dexamethasone‐cholesteryl hemisuccinate attenuates chronic inflammation condition in tumor‐bearing mice. The attenuation of inflammation inhibits interorgan crosstalk of immunosuppressive myeloid‐derived suppressor cells and reactivates the antitumor immunity. This strategy shows synergistic antitumor effects with immune checkpoint inhibitors. The proposed strategy is described here as a "Reprogramming of Immunoreaction in Spleen and Extra‐parenchyma in Tumor; RISET."